Aspects regarding speed development in football game in 12 - 14 years old children - Sorin BUHAȘ; Grigore Vasile HERMAN; Mirela ȘTEF (Editura Universităţii din Oradea, 2018)
Football in schools, top level football, or football for masses have a wide range of issues studied by theory and methodology in order to render these football branches more effective, and to find other ways or means to achieve in optimal conditions the objectives of this sports area. Football theory comprises a wide array of knowledge structured into a coherent and logical system that describes and explains this phenomenon. Thus, theory is divided into two notions, one being the description of the content, and the other, its explanation. Football methodology takes over and adapts some general principles, methods and means of pedagogy, physical education, sports, sports training, but also of sports games methodology. It also includes principles, methods and means of training in football. In schools, football is part of the curriculum. In this context, we aim to study some aspects of speed development using football and its specific methods as intervention means. The age category we have addressed is represented by children aged 12-14 years. We chose to study speed development because it is an extremely important element in the acquisition of motor skills at this specific age in children.